2020
DOI: 10.1111/rda.13827
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gonadal macroscopic and microscopic morphometry reveals precocious puberty in Bísaro pig

Abstract: Bísaro pig (BP) population has grown in numbers in the last decade, representing today one of the most important Portuguese livestock breeds (Paixao et al., 2018). Yet, the high-end cured products, which drove this growth, no longer represent the major production of this breed. Difficulties to comply with EU welfare regulations are being pointed out as the main factor involved in this phenomenon. This is especially important when it refers to surgical castration restrictions introduced by the Council Directive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(37 reference statements)
2
8
0
Order By: Relevance
“…Histological analysis showed that diameter of the seminiferous tube, lumen area, number of Leydig, and Sertoli and germ cells were larger in 30-day-old and 120-day-old HZ boar than those of LC boar of the same age, and sperm were observed in 120-day-old HZ boar ( Figure 1 ). HZ boar underwent puberty development at an earlier stage than LC boar and demonstrated early sexual maturity, which is consistent with some other local pig breeds (such as Bísaro pig [ 49 ], Meishan pig [ 6 ]).…”
Section: Discussionsupporting
confidence: 85%
“…Histological analysis showed that diameter of the seminiferous tube, lumen area, number of Leydig, and Sertoli and germ cells were larger in 30-day-old and 120-day-old HZ boar than those of LC boar of the same age, and sperm were observed in 120-day-old HZ boar ( Figure 1 ). HZ boar underwent puberty development at an earlier stage than LC boar and demonstrated early sexual maturity, which is consistent with some other local pig breeds (such as Bísaro pig [ 49 ], Meishan pig [ 6 ]).…”
Section: Discussionsupporting
confidence: 85%
“…The values of morphological parameters (the perimeter and area of the tubular lumen) in HZ boars were greater than those in LC boars in the 1 M, 3 M, 4 M, and 6 M groups, suggesting that seminiferous tubular lumen appears earlier in HZ boars than in LC boars. In conclusion, histological analyses revealed that Chinese HZ boars have an earlier onset of puberty and earlier testicular development compared to LC boars [33], which is in agreement with other indigenous porcine breeds [36,37].…”
Section: Discussionsupporting
confidence: 83%
“…Absolute dimensions from in vivo and post-mortem measurements were compared to the expected pubertal dimensions of this specific breed [32]. Eleven animals were kept as intact males throughout the whole experiment (GrpC; n = 11) to establish age-match scrotal dimensions.…”
Section: Measurementsmentioning
confidence: 99%
“…The Bísaro pig is one of the most representative Portuguese autochthonous breeds [29,30] and is known for its robustness and reported meat quality [31]. The BP is sexually precocious, reaching puberty between 14 and 17 weeks old [32]. If intended for the industry of cured value-added products, it is mainly reared up to 13 months old.…”
Section: Introductionmentioning
confidence: 99%